2016
DOI: 10.1519/jsc.0000000000000785
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content and Density Among Female NCAA Division I Athletes Across the Competitive Season and Over a Multi-Year Time Frame

Abstract: Stanforth, D, Lu, T, Stults-Kolehmainen, MA, Crim, BN, and Stanforth, PR. Bone mineral content and density among female NCAA Division I athletes across the competitive season and over a multi-year time frame. J Strength Cond Res 30(10): 2828-2838, 2016-Longitudinal and cross-sectional bone mineral content (BMC) and bone mineral density (BMD) comparisons were made among impact and nonimpact sports. Female collegiate athletes, 18-23 years of age, from basketball (BB; n = 38), soccer (SOC; n = 47), swimming (SW; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…Bone mineral density (BMD) is known to vary among athletes who participate in different sports. In general, BMD tends to be lower in those who participate in weight‐supported (eg, cycling) or low‐impact activities (eg, cross‐country skiing) than in athletes who participate in higher‐impact activities (eg, volleyball) . This suggests that forces acting on bone in low‐impact and non‐impact sports are not sufficient to generate the anabolic skeletal response that occurs with high‐impact activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone mineral density (BMD) is known to vary among athletes who participate in different sports. In general, BMD tends to be lower in those who participate in weight‐supported (eg, cycling) or low‐impact activities (eg, cross‐country skiing) than in athletes who participate in higher‐impact activities (eg, volleyball) . This suggests that forces acting on bone in low‐impact and non‐impact sports are not sufficient to generate the anabolic skeletal response that occurs with high‐impact activities.…”
Section: Introductionmentioning
confidence: 99%
“…In general, BMD tends to be lower in those who participate in weight-supported (eg, cycling) or low-impact activities (eg, cross-country skiing) than in athletes who participate in higher-impact activities (eg, volleyball). (1)(2)(3) This suggests that forces acting on bone in low-impact and non-impact sports are not sufficient to generate the anabolic skeletal response that occurs with high-impact activities. However, bone loss has been observed over time in some athletes, at an age when stable BMD would be expected, suggesting that exercise may sometimes have catabolic skeletal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is known to be a factor in promoting bone formation and moderate levels of physical activity, as little as twice per week, have been shown to reduce the risk of fractures [2]. Athletes, regardless of sport, have higher bone mineral density than non-athletes [3,[6][7][8], and BMD is higher in athletes engaged in high impact sports such as basketball and volleyball than in athletes in low-impact or non-impact sports such as swimming, water polo, and distance running [5][6][7][9][10][11][12]. Although sports with high-impact loading are associated with higher bone mineral density than low-impact or non-impact sports, confounding variables are differences in the athletes' body size and sport-specific training [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this comes from the finding that BMD did not differ between dancers and cheerleaders at any of the sites measured. Previous studies have shown a sport specific response to loading patterns in bone mineral density [6,9,11,29]. Team female team handball players had higher forearm BMD, considered to be a weight-bearing site in this sport, than female soccer players [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation